2019
DOI: 10.1002/14651858.cd003809.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Fluorides for preventing early tooth decay (demineralised lesions) during fixed brace treatment

Abstract: Fluorides for preventing early tooth decay (demineralised lesions) during fixed brace treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 69 publications
2
49
0
6
Order By: Relevance
“…In summary, we were able to show, by means of the clinical use of cross-sectional OCT imaging, that clinically relevant sealant damages developed in popular surface sealants already 3 months after application. Thereby conforming the results of other clinical studies [7,11,12,[17][18][19]25], we believe that the protective effect against demineralization by orthodontic surface sealants may be limited in time, and further preventive measures should be investigated. Table 3 Scores for sealant integrity loss at 3, 6, 9 and 12 months Clin Oral Invest…”
Section: Discussionsupporting
confidence: 86%
“…In summary, we were able to show, by means of the clinical use of cross-sectional OCT imaging, that clinically relevant sealant damages developed in popular surface sealants already 3 months after application. Thereby conforming the results of other clinical studies [7,11,12,[17][18][19]25], we believe that the protective effect against demineralization by orthodontic surface sealants may be limited in time, and further preventive measures should be investigated. Table 3 Scores for sealant integrity loss at 3, 6, 9 and 12 months Clin Oral Invest…”
Section: Discussionsupporting
confidence: 86%
“…(Marinho et al, 2003) This study showed that 53.1% of the individuals used fluoride containing toothpaste and these patients showed lesser incidence of caries exhibiting lower DMFT scores. (Benson et al, 2019) Increased fluoride use can lead to discoloration of the tooth surface, but there is very less differential complaints and unwanted effects such as soft tissue damage and tooth staining were minimal for the use of fluoride over 1000ppm. (Rasines, 2010) This study shows and exhibits various oral health education techniques with room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding suggests that the severe cariogenic challenge around orthodontic appliances appears to require more fluoride than that delivered by the low fluoride concentrations in water and by the 1,100-ppm fluoride dentifrice. In fact, it is evidenced that the use of professional methods of topical fluoride application, overcomes the preventive effects of the single-use of self-administrated (fluoride toothpaste) method in patients wearing orthodontic appliances; however, the level of evidence regarding the fluoride professional therapies against ACL is low (18). With this in mind, it must be pointed out that the diffusion and dissolution processes of this salivary ion on the tooth-pellicle-biofilm-saliva interface in individuals who do and who do not develop ACL should be investigated in detail considering the fluoride therapy.…”
Section: Discussionmentioning
confidence: 99%